2008
DOI: 10.1182/blood-2008-04-148692
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen inhibits dendritic cell maturation to RNA viruses

Abstract: Dendritic cells (DCs) play a central role in initiating and polarizing the immune response. Therefore, DC maturation represents a key control point in the shift from innate to adaptive immunity. It is suspected that during pregnancy, hormones are critical factors that modulate changes reported to occur in maternal immunity. Here we examined the effect of 17-beta-estradiol (E2) on the maturational response triggered by virus in human DCs and its influence on their ability to activate naive T cells. We developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 50 publications
3
48
1
Order By: Relevance
“…Notably, estrogen has also been shown to downregulate the antiviral response to RNA viruses in dendritic cells by suppressing the production of type I interferon 49 . It is plausible that estrogen affects the production of type I interferon in response to viral infection partly because of its effect on caspase-12 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, estrogen has also been shown to downregulate the antiviral response to RNA viruses in dendritic cells by suppressing the production of type I interferon 49 . It is plausible that estrogen affects the production of type I interferon in response to viral infection partly because of its effect on caspase-12 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Type I and type III IFN secretion and interferon stimulated genes (ISGs) expression by human uterine ECs is unaffected by E 2 concentration, which suggests that IFN-mediated protection at the epithelium is relatively constant across the menstrual cycle (Patel et al, 2012). However, other studies have shown an effect on IFN and ISG expression by E 2 , which indicates that the interaction of hormone and IFN response pathway is complex and may depend on cell type and location within the FRT (Escribese et al, 2008;Li et al, 2001). Previous studies have demonstrated a role for hormonal regulation of antimicrobial and cytokine production in vivo in the FRT.…”
Section: Influence Of Sex Hormones On Cytokines Chemokines and Antimmentioning
confidence: 93%
“…E2 also regulates innate immune responses, including production of proinflammatory cytokines, by selectively up-and downregulating microRNA (miRNA) (44). Estradiol affects the differentiation and functioning of APC, including DC (45,46). E2 can have bipotential effects on inflammatory responses, with low doses enhancing proinflammatory cytokine production (e.g.…”
Section: Sex Steroidsmentioning
confidence: 99%